Association of pancreatitis with risk of diabetes: analysis of real-world data - Ba, Djibril M.; Chinchilli, Vernon M.; Cozzi, Anna M.; Bradley, David P.; Pichardo-Lowden, Ariana R. (Frontiers in Clinical Diabetes and Healthcare, 2024)
Introduction Diabetes is a major cause of disease burden with considerable public health significance. While the pancreas plays a significant role in glucose homeostasis, the association between pancreatitis and new onset diabetes is not well understood. The purpose of this study was to examine that association using large real-world data. Materials and methods Utilizing the IBM® MarketScan® commercial claims database from 2016 to 2019, pancreatitis and diabetes regardless of diagnostic category, were identified using International Classification of Diseases, Tenth Revision [ICD-10] codes. We then performed descriptive analyses characterizing non-pancreatitis (NP), acute pancreatitis (AP), and chronic pancreatitis (CP) cohort subjects. Stratified Cox proportional hazards regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CI) of diabetes across the three clinical categories. Results In total, 310,962 individuals were included in the analysis. During 503,274 person‐years of follow‐up, we identified 15,951 incident diabetes cases. While men and women had higher incidence rates of CP and AP-related diabetes, the rates were significantly greater in men and highest among individuals with CP (91.6 per 1000 persons-years (PY)) followed by AP (75.9 per 1000-PY) as compared to those with NP (27.8 per 1000-PY). After adjustment for diabetes risk factors, relative to the NP group, the HR for future diabetes was 2.59 (95% CI: 2.45-2.74) (P<0.001) for the CP group, and 2.39 (95% CI: 2.30-2.48) (P<0.001) for the AP group. Conclusion Pancreatitis was associated with a high risk of diabetes independent of demographic, lifestyle, and comorbid conditions.